The political ecology of tropical forests in Southeast Asia: historical perspectives - Tuk-Po, L.; Jong, W. de; Ken-Ichi, Abe (Kyoto University Press, 2003)
A simplistic explanation of why tropical forests degrade or disappear all together is, because loggers take out too many trees, companies convert forest for plantations, and small farmers slash forest to make agricultural fields. Political ecology is a scientific inter-discipline that tries to identify the political dimension of forest resource appropriation, contestation over forest benefits, and the role of power and discourse in the processes of unsustainable use and resulting forest degradation. This chapter summarizes ten chapters in the volume in which it is published. Several of chapters demonstrate that modern struggles over forests have their roots in colonial periods. Colonial powers used force, but also the argument that deforestation negatively affected the local climate, to expulse forest farmers from timber rich forest lands. Often control of the trade of lucrative forest products like rattan was decided by force. In these struggles, colonial powers used force against local Sultans, local Sultans used force against forest dwellers, and powerful forest dweller groups used force against weaker groups, concludes de Jong in his chapter. In the modern day tropical forest landscape in Asia the actors have change, but many of the processes of contestation remain the same. National rulers, like Suharto in Indonesia, gave away forest concessions to business cronies and the military for the sake of national economic development, but equally often to win political support. Under the recent decentralisation wave, control over forests is now increasingly contested at lower government levels, or even at the village level among forest dwellers with different ethnic affiliations, as Steve Rhee, demonstrates in his chapter. The political ecology of Asia’s tropical forest also has a wider international dimension, and it is not only confined to underdeveloped countries. Fred Gale discusses in his chapter the history of the International Timber Organization. ITTO was set up to advance the cause of tropical timber producing countries, in the face of increasing international concern of the affect of unsustainable logging. In order to adequately represent its interests, ITTO developed and disseminated the sustainable logging discourse. John Knight in his chapter demonstrates that modern problems of a forest dependent population that suffers from the impact of contemporary economic development thinking also happen in Japan. Traditional Japanese timber producers grow high value trees that are used in ritually enshrined housing construction. The mass import of foreign, tropical timber not only negatively affects their livelihood. Japanese timber growers loose maintain their traditions and cultural identity that were closely linked to their forestry existence.